Comparative study of government datasets of Brazil and Colombia, with data of agriculture and rural development - Reyes, Jacquelin Teresa Camperos [UNESP]; Sant'Ana, Ricardo Cesar Gonçalves [UNESP]; Segundo, José Eduardo Santarém (Servicio de Publicaciones de la Universidad de Murcia, 2018)
This document analyzes agricultural and rural development datasets of the Brazilian and Colombian governments, questioning, from open data principles, if these datasets are indeed available as open data. It was performed an analysis of datasets observing the adherence of some of the open data principles created in the city of Sebastopol, United States. Brazilian datasets are published in structured and non-proprietary files. Colombia has both a greater number of published datasets and a greater variety in the subjects of such data, however, in relation to Brazil, it must still work in that the data is in machine-readable and non-proprietary structured formats. It is proposed to develop new researches aimed at the enhancement of evaluation mechanisms of government datasets, to verify the openness of the data under prisms like those of Sebastopol, even the creation of new models, focusing socioeconomic contributions that arise from researches of Information Science professionals.
Estudo comparativo de datasets governamentais do brasil e da colômbia, com dados de agricultura e desenvolvimento rural
Keywords: Brazil data; Colombia data; Datasets; Open government data; Principles of Sebastopol